ZnFe2O4/C composite nanometer fiber super capacitor electrode material and preparation method thereof - HAN ZHENZHEN; CAO BINGQIANG; SUN JING; YANG SHUHUA (2017)
The invention discloses a ZnFe2O4/C composite nanometer fiber super capacitor electrode material and a preparation method thereof; the preparation method comprises the following steps: using a magnetic stirring method to evenly spread ferric chloride hexahydrate, waterless zinc chloride and PAN into a DMF solution; then using a static spinning technology to prepare a PAN/Znl2/FeCl3 precursor composite nanometer fibrofelt, and drying same; finally, carrying out three steps of heat treatments for the dried sample so as to obtain the ZnFe2O4/C composite nanometer fiber super capacitor electrode material, wherein the heat treatments comprise pre-oxidation treatment, low temperature air atmosphere calcining, and high temperature Ar atmosphere calcining. The prepared ZnFe2O4/C composite nanometer fiber is an ultrafine continuous fiber with a stable frame structure, the fiber diameter is controlled as dozens of nanometer to hundreds of nanometer, and the ZnFe2O4/C nanometer particles embedded in the fiber are evenly